Gender and age as moderators in the service evaluation process - Sharma, Piyush; Chen, I.S.; Luk, S.T. (Emerald Group Publishing, 2012)
Purpose – Prior research exploring the relationships among sacrifice, service quality, value, satisfaction, and behavioral intentions in service evaluation models did not consider customer characteristics. This study aims to test the moderating effects of two demographic variables (i.e. gender and age) on all the relationships in the “comprehensive” service evaluation model.Design/methodology/approach – Responses from a diverse group of shoppers (n ¼ 2,727) in six retail categories (cosmetics, electronics, fashion, jewelry, telecom services, and department stores) were examined using structural equation modeling.Findings – The negative relationship between sacrifice and perceived value, and the positive association of perceived value and satisfaction with behavioral intentions, is stronger for the male and older customers; whereas the positive association of service quality with satisfaction and value is stronger for female and younger customers.Research limitations/implications – The study examined behavioral intentions instead of actual behavior due to its cross-sectional design. However, in the categories examined (cosmetics, fashion, department stores, etc.) where purchase frequencies range from moderate to high, behavioural intentions may highly correlate with actual behavior.Practical implications – The findings help retail managers understand the differences in the influence of perceived sacrifice, value, service quality, and satisfaction on the behavioral intentions of customers, based on individual characteristics such as gender and age. They should be able to plan and prioritize their marketing activities for diverse customer segments.Originality/value – The study offers new insights on the individual differences in the service expectations and perceptions, which in turn affect customer behavior and loyalty.